2017
DOI: 10.1002/jwmg.21318
|View full text |Cite
|
Sign up to set email alerts
|

Landscape influence on dispersal of yearling male white‐tailed deer

Abstract: Landscape features can alter the transfer phase of dispersal and dispersal‐mediated disease transmission and gene flow. The transfer phase is poorly understood, but improved understanding of landscape effects on dispersal distance and direction would allow better prediction and mitigation of disease spread and improved delineation of management zones. To investigate how ecological settings influence dispersal in white‐tailed deer (Odocoileus virginianus), we captured and radio‐collared 409 juvenile male deer f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 58 publications
4
18
0
3
Order By: Relevance
“…rivers, highways) as being semipermeable to gene flow (Kelly et al, 2014; Locher et al, 2015; Miller et al, 2020; Robinson et al, 2012). This, despite the potential complication caused by re-stocking efforts, and in accordance with radio-telemetry data (Peterson et al, 2017).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…rivers, highways) as being semipermeable to gene flow (Kelly et al, 2014; Locher et al, 2015; Miller et al, 2020; Robinson et al, 2012). This, despite the potential complication caused by re-stocking efforts, and in accordance with radio-telemetry data (Peterson et al, 2017).…”
Section: Discussionsupporting
confidence: 87%
“…However, many of these studies relied upon (now) obsolescent molecular markers (e.g., mtDNA or reduced panels of microsatellite DNA markers) that captured substantially less polymorphism than do next-generation methods (Hodel et al, 2017;Jeffries et al, 2016;Lemopoulos et al, 2019). Subsequent studies at finer spatial scales have supported the role of large-scale geomorphic configurations (e.g., rivers, highways) as semipermeable barriers to WTD gene flow (Kelly et al, 2014;Locher et al, 2015;Miller et al, 2020;Robinson et al, 2012), despite the potential complication caused by restocking efforts, and in accordance with radio-telemetry data (Peterson et al, 2017).…”
Section: Landscape-drivers Of Contemporary Population Structurementioning
confidence: 92%
“…The overall dispersal rate (55%) was lower than rates reported in Pennsylvania (68–70%; Long et al ); however, we observed a greater proportion of fall dispersal (83%) relative to spring dispersal (17%) than has been reported elsewhere (Long et al ). Spring dispersal is thought to be influenced by population structure (Hölzenbein and Marchinton ; Long et al , ) with spring dispersal becoming less common as density of adult females decreases and fall dispersal more common as density of adult males increases (Shaw et al , Long et al , Peterson et al ). The seasonality of dispersal timing we observed may suggest strong male–male competition in the study area (Rosenberry et al ), with limited female aggression towards yearling males.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the influence of different deer population objectives in neighboring management units would have less effect on large WMUs than on small county units. In addition to the effect of unit size, use of roads and rivers as boundaries may act as semi‐permeable barriers to emigration and immigration, further reducing the influence of emigration and immigration on overall population parameters within WMUs compared with county‐based units (Rosenberry et al , McCoy et al , Long et al , Peterson et al ). Wildlife management units may reduce expected variation by reducing the influence of neighboring management units due to larger area and semi‐permeable nature of physical boundaries.…”
Section: Discussionmentioning
confidence: 99%